The Relevance of the Market and News Direction When Analyzing the Inflation News Impact on the US Stock Market - JareÃ±o, Francisco; Tolentino, Marta; Torrecillas, MÂª del Camino (International Journal of Economics and Financial Issues, 2018)
This study aims to measure the inflation news impact on common sector stock returns. Using CPI and PPI announcements and daily returns of S&P500 Index, an Event Study Methodology analysis of a sample period from January 1990 to April 2013 is conducted. Taking into account the direction of the inflation news and the state of the economy, sector returns seem to react strong to CPI announcements and do not react to PPI announcements. In addition, the majority of the significant responses occur two days after that the inflation announcement takes place, so investors may react later to the arrival of new information. Finally, inflation announcements appear to have an impact when the state of the economy is low and when the direction of news is negative. Therefore, the state of the economy and direction of surprises are central variables to analyses of inflation news effects on abnormal returns. Keywords: Inflation announcement; Flow-through ability; Stock return; market efficiency JEL Classifications: E31, G12, G3, L2